2020
DOI: 10.1111/joim.13125
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Fabry mutations in clinical practice: a closer look at α‐galactosidase A‐3D structure

Abstract: Background. Fabry disease (FD) is an X-linked lysosomal storage and multi-system disorder due to mutations in the a-galactosidase A (a-GalA) gene. We investigated the impact of individual amino acid exchanges in the a-GalA 3D-structure on the clinical phenotype of FD patients. Patients and methods. We enrolled 80 adult FD patients with a-GalA missense mutations and stratified them into three groups based on the amino acid exchange location in the a-GalA 3Dstructure: patients with active site mutations, buried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Fabry disease (FD) is a rare X-linked lysosomal storage disorder caused by a variety of mutations in the alpha-galactosidase gene ( GLA) on Xq21.3-q 22. The result of which is a wide spectrum of α-GAL enzyme activities, ranging from normal to complete deficiency [1] , leading to different clinical phenotypes with both intra- and interfamilial clinical variabilities [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Fabry disease (FD) is a rare X-linked lysosomal storage disorder caused by a variety of mutations in the alpha-galactosidase gene ( GLA) on Xq21.3-q 22. The result of which is a wide spectrum of α-GAL enzyme activities, ranging from normal to complete deficiency [1] , leading to different clinical phenotypes with both intra- and interfamilial clinical variabilities [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“… b 1 = benign, 2 = likely benign, 3 = VUS, 3+ = VUS with probable pathogenicity, 4 = likely pathogenic, 5 = pathogenic (Kolokotronis et al, 2020 ; Richards et al., 2015 ). c active site mutation = variant in the active site of the alpha‐galactosidase A, buried mutation = variant close to active site, other mutation = variant outside the active site (Rickert et al, 2020 ). …”
Section: Resultsmentioning
confidence: 99%
“…The allocation to these classes was achieved by evaluating the information from Alamut Visual version 2.11 (Interactive Biosoftware, Rouen, France) providing the data of various population and mutation databases, different prediction tools, as well as information from the literature. (3) Based on the localization of missense variants (i.e., amino acid substitutions) in the final enzyme defining the categories of mutations found in the “active site”, “buried” mutations, and “other” mutations (Garman & Garboczi, 2004 ; Rickert et al, 2020 ); for this, the 3D‐structure of GAL obtained from the Protein Data Bank (PDB) in Europe ( https://www.rcsb.org/structure/1R46 2003) was analyzed in PyMOL 1.8 graphics system (Delano, 2015 ). For each missense variant, the individual localization of the amino acid exchange in the final enzyme was determined.…”
Section: Methodsmentioning
confidence: 99%
“…The first domain contains the active site and extends from residues 32 to 330, and the second domain is comprised of residues 331-429, burying much surface area within one monomer. Rickert et al [ 6 ] found that patients with active site or buried mutations showed a severe phenotype with multi-organ involvement and early disease manifestation. Patients with other mutations had a milder phenotype with less organ impairment and later disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with active site or buried mutations showed a severe phenotype with multi-organ involvement and early disease manifestation. Patients with certain mutations showed a milder phenotype with less organ impairment and later disease onset[ 6 ]. In male patients, the α-GLA enzyme activity is often significantly decreased, while about a third of female patients have enzymes within the normal range.…”
Section: Introductionmentioning
confidence: 99%